Role of medical rehabilitation in postpoliomyelitis syndrome. A case report - Dogaru, Gabriela Bombonica; Stănescu, Ioana (Medicine and Pharmacy Reports, 2013)
Postpoliomyelitis syndrome is characterized by a sudden or progressive loss of muscle strength, muscle atrophy, muscle pain, fatigue, intolerance to cold, after a period of at least 15 years from the acute polio virus infection, a period of neurological and functional stability. No therapeutic benefit of the evaluated drug agents (pyridostigmine, steroids, amantadine) has been reported. The reason for this presentation results from the fact that clinical studies have demonstrated that isokinetic and isometric muscle training can prevent the loss of muscle strength and reduce muscle fatigue. Rehabilitation programs through physical-kinetic therapy are the only way to limit functional deficit, playing an important role in the long-term management and care of patients. The particularity of this case is the fact that the symptoms occurred after a 40 year period of neurological stability. The regular monitoring and inclusion of the patient in complex medical rehabilitation programs are important in order to limit the functional deficit and increase the quality of life of these patients.